2010
DOI: 10.3233/jad-2010-091672
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Cognitive Assessment in Primary Care to Identify Patients with Suspected Cognitive Impairment

Abstract: The incidence and prevalence in those over age 65 of neurodegenerative disorders and chronic diseases, which often have deleterious effects on cognition, are rapidly increasing in western societies. Primary care physicians (PCPs) provide the majority of medical treatment for older people and in order to effectively care for their patients with suspected cognitive impairment, they must have tools that will allow them to accurately assess their patient's cognitive function. This knowledge will assist the PCPs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 57 publications
0
46
0
1
Order By: Relevance
“…56 The authors of the review concluded that the Hopkins Verbal Learning Test had better sensitivity for the detection of MCI in older adults than the computerised tests. They also identified that one automated test, CogState, enabled the identification of cognitive deficits beyond mild impairments in memory; for example, CogState detected more functional deficits than the Hopkins Verbal Learning Test or MMSE.…”
Section: Index Testmentioning
confidence: 99%
See 4 more Smart Citations
“…56 The authors of the review concluded that the Hopkins Verbal Learning Test had better sensitivity for the detection of MCI in older adults than the computerised tests. They also identified that one automated test, CogState, enabled the identification of cognitive deficits beyond mild impairments in memory; for example, CogState detected more functional deficits than the Hopkins Verbal Learning Test or MMSE.…”
Section: Index Testmentioning
confidence: 99%
“…They also identified that one automated test, CogState, enabled the identification of cognitive deficits beyond mild impairments in memory; for example, CogState detected more functional deficits than the Hopkins Verbal Learning Test or MMSE. 56 The authors, however, did not address if these tests had the potential to facilitate timely diagnosis or if they were effective in monitoring disease progression. Appendix 1 explains measures for assessing an index test against a reference standard.…”
Section: Index Testmentioning
confidence: 99%
See 3 more Smart Citations